Integrative radiogenomic analysis for genomic signatures in glioblastomas presenting leptomeningeal dissemination. Issue 27 (July 2016) - You, Hye Jin; Park, Ho-Young; Kim, Jinkuk; Lee, In-Hee; Seol, Ho Jun; Lee, Jung-Il; Kim, Sung Tae; Kong, Doo-Sik; Nam, Do-Hyun
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Despite therapeutic advances, the prognosis for glioblastoma (GBM) remains poor. In particular, leptomeningeal dissemination (LMD) has a dismal prognosis. The aim of this study was to identify tumor molecular phenotype, which has a great propensity to develop LMD. Between May 2004 and December 2012, a total of 145 GBM tumor samples were obtained from data registry. A total of 20 of the 145 patients with GBM were found to develop LMD. A specialized radiologist confirmed the diagnosis of LMD on magnetic resonance imaging. To clarify the genomic signatures in GBM with LMD, we performed integrative analysis of whole transcriptome sequencing and copy number alteration in the radiological features indicating LMD phenotypes in GBM. Eleven newly diagnosed patients with GBM with LMD had worse prognosis than those without LMD (median 5.55 vs. 12.94 months, P  < 0.0001). Integrating analysis using gene expression based on the change of copy number revealed that SPOCK1, EHD2, SLC2A3, and ANXA11 were highly expressed with the gain of copy number, compared with the gene expression in the non-LMD group. In addition, it was demonstrated that NME2, TMEM100, and SIVA1 were downregulated with the loss of copy number. We also found that mesenchymal subtype accounted for 50% in LMD group, whereas mesenchymal subtype consisted of 29% in non-LMD group, even though there was no statistical significance ( P = 0.06). Through this radiogenomic analysis, we suggested the possibility of finding candidate genes associated with LMD and highlighted the significance of integrating approach to clarify the molecular characteristics in LMD.